The impacts of new antidiabetic drugs on the risk of ischemic and hemorrhagic strokes: a comprehensive review and meta-analysis of clinical trials - Azhari, Hala F.; Dawson, Jesse (Frontiers in Stroke, 2024)
Introduction: New classes of antidiabetic drugs reportedly lower the risk of cardiovascular events. This review summarizes the evidence for the effect of these drugs on risk of strokes in diabetics individual. Methods: Multiple databases that reported stroke outcome data were scrutinized for clinical trials (from inception to June 25, 2023), compared sodium glucose cotransporter 2 inhibitors (SGLT2-Is), glucagon like peptide 1 receptor agonists (GLP1-RAs), and dipeptidyl peptidase 4 inhibitors (DPP4-Is) versus other antidiabetic drugs and placebo. Results: Among the 960 identified trials, 259 satisfied the eligibility criteria. Among these, 177 and 82 trials reported at least one or no stroke events, respectively. In total, 208, 19, and 32 trials had a low, unclear, and high risk of bias, respectively. SGLT2-Is use did not decrease the risk of non-fatal hemorrhagic or ischemic stroke (risk ratio (RR) 0.96; 95% CI 0.86 to 1.06; P = 0.41) versus either active comparators or placebo. GLP1-RAs use significantly decreased stroke risk (RR 0.84; 95% CI 0.77 to 0.93; P = 0.0005) and ischemic stroke (RR 0.85; 95% CI 0.77 to 0.94; P = 0.002) versus placebo. However, GLP1-RAs use did not decrease hemorrhagic events versus active comparators or placebo. DPP4-Is use did not decrease the risk of non-fatal hemorrhagic or ischemic stroke (RR 0.91; 95% CI 0.83 to 1.01; P = 0.07) versus active comparators or placebo. For all classes, fatal stroke risk did not decrease versus active comparators or placebo, and the GRADE scores were moderate. Discussion: Use of GLP1-RAs, but not SGLT2-Is or DPP4-Is, may decrease non-fatal stroke risk. In consideration of the results, the findings may inform the treatments of diabetic people at risk of strokes and the design of new antidiabetic interventional trials.